2011
DOI: 10.1097/fjc.0b013e31821c832f
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency-induced Hypertension Is Associated With Vascular Oxidative Stress and Altered Heart Gene Expression

Abstract: Vitamin D deficiency (VDD) is associated with an increased cardiovascular risk. We investigated the effect of VDD on the cardiovascular system of growing male rats fed with a vitamin D-deficient diet. Using isolated rat aorta, we assessed both superoxide anion and endothelial-dependent relaxations. Microarray technology was used to identify changes induced by VDD in cardiac gene expression. Compared with control, VDD increased systolic blood pressure (P < 0.05) and superoxide anion production in the aortic wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 46 publications
2
42
0
4
Order By: Relevance
“…39 VDD was related to higher vascular oxidative stress. 33 In the present study, VDD was associated not only with increased reactive oxygen species in the cardiac tissue, as shown by the higher lipid hydroperoxide, but also with reduced activity of catalase and glutathione peroxidase. It is important to consider a possible mechanism to compensate the increased oxidative stress that occurs through the Nrf-2 pathway.…”
Section: [Oh]supporting
confidence: 60%
See 1 more Smart Citation
“…39 VDD was related to higher vascular oxidative stress. 33 In the present study, VDD was associated not only with increased reactive oxygen species in the cardiac tissue, as shown by the higher lipid hydroperoxide, but also with reduced activity of catalase and glutathione peroxidase. It is important to consider a possible mechanism to compensate the increased oxidative stress that occurs through the Nrf-2 pathway.…”
Section: [Oh]supporting
confidence: 60%
“…Therefore, some studies have shown that VDD can influence energetic metabolism, 29 inflammation, [30][31][32] and oxidative stress. 33 These changes are part of the cardiac remodeling process.…”
Section: [Oh]mentioning
confidence: 99%
“…Our study provides direct molecular insight to previously published observations that have suggested that vitamin D 3 deficiency-induced hypertension is associated with vascular oxidative stress. 29 It is well documented that oxidative stress is involved in vascular complications and development of hypertension. 30 Oxidative and nitroxidative stress impairs endothelium-dependent relaxation of the blood vessels and is involved in the facilitation of smooth muscles contractions.…”
mentioning
confidence: 99%
“…29 However, none of these studies provided any direct proof of how vitamin D 3 improves NO production and decreases nitroxidative stress. Our studies are not only coherent with previous observations, but provide new direct evidence, on the molecular level, why vitamin D 3 can be highly beneficial for the treatment of a dysfunctional cardiovascular system.…”
mentioning
confidence: 99%
“…Several studies report a linkage between VDD and up-regulation of RAS, oxidative stress and endothelial dysfunction (3,10,20,28). By means of flow mediated dilation and serum TBARS in asymptomatic subjects, Tarcin et al have shown that VDD is associated with endothelial dysfunction and increased lipid peroxidation (27).…”
Section: Discussionmentioning
confidence: 99%